Hindrances Faced by Literacy Mobilizers While Promoting Non-Formal Education Programs: A Case Study - Naseem, Farhat (IJLTP, 2025)
Literacy mobilizers face several hindrances while propagating NFE programs to improve the literacy rate in the marginalized communities. This qualitative case study was conducted to explore the hindrances faced by Literacy Mobilizers to promote Non-Formal Education (NFE). The population of this study was 335 Literacy Mobilizers of Punjab, out of which 07 purposively selected Literacy Mobilizers were participants in this research. Interview was utilized to collect data from Literacy Mobilizers. Thematic analysis was done for data Analysis. Major findings of the study revealed that Literacy Mobilizers face hindrances regarding religious belief system, gender roles, access to community, government support, community motivation and community participation while promoting an NFE program. A participatory approach may be utilized by literacy mobilizers while organizing and executing NFE programs to increase community motivation and participation. Moreover, continuous capacity-building training programs may be conducted by stakeholders to train Literacy Mobilizers to cope with the hindrances faced while promoting NFE programs.